178k views
22 votes
Formulate a step-by-step explanation on how to perform operations on functions. Use the problem in the picture to use to explain each step.

Type your response as follows:
Step 1:
Step 2:
.
.
and so on.

Formulate a step-by-step explanation on how to perform operations on functions. Use-example-1

1 Answer

10 votes

Answer:

k(x) - h(x) = (3x + 7)

Explanation:

Given functions are,

h(x) = x - 5

k(x) = 4x + 2

We have to find k(x) - h(x).

Step I

k(x) - h(x) = (4x + 2) - (x - 5)

Step II

Combine like terms,

k(x) - h(x) = (4x - x) + (2 + 5)

Step III

k(x) - h(x) = 3x + 7

Hence, k(x) - h(x) = (3x + 7) is the answer.

User Superbob
by
5.7k points